2017
DOI: 10.1016/j.apmr.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Body Image in Patients With Spinal Cord Injury During Inpatient Rehabilitation

Abstract: During participants' first inpatient rehabilitation stay after SCI, body image progressed toward a healthier state. Body image explains part of the variance in depression and anxiety, and the entire rehabilitation team should be targeting interventions to improve body image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
1
9
0
4
Order By: Relevance
“…Individuals with SCI and their partners were both least satisfied with their 'sexual life', which is in accordance with earlier research [15,18,40]. It is likely that the SCI and related physical (e.g., bladder and/or bowel incontinence) [2] and mental (e.g., impaired body image) [41] problems influence their sexual relationship [42].…”
Section: Mental Health and Life Satisfaction: Relationship And Comparsupporting
confidence: 87%
“…Individuals with SCI and their partners were both least satisfied with their 'sexual life', which is in accordance with earlier research [15,18,40]. It is likely that the SCI and related physical (e.g., bladder and/or bowel incontinence) [2] and mental (e.g., impaired body image) [41] problems influence their sexual relationship [42].…”
Section: Mental Health and Life Satisfaction: Relationship And Comparsupporting
confidence: 87%
“…We surmise that this may have been less relevant to the participants in our study as the median time since SCI was 15 years. 22 This was the experience of one the authors with a lived experience with SCI: she initially did not like to wear a leg bag, or have a bump showing where the catheter bag was, however after 21 years, she now feels this issue is easy to manage simply by choosing the proper clothing. While limiting fluids is a common behavior among people with SCI (as it can help to reduce the frequency of CIC and limit incontinence) our results would suggest that this is not a high priority concern compared to the other issues.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reductions in general distress were also observed, although the majority of participants still reported significant distress at the end of rehabilitation. Several studies have also identified average improvements in depressive symptoms (Craig et al, 2017a; Kennedy et al, 2010; van Diemen et al, 2017; White et al, 2010), anxiety symptoms (van Diemen et al, 2017), and life satisfaction (van Koppenhagen et al, 2009; White et al, 2010) during inpatient rehabilitation. Altogether, these findings indicate that, although the psychological adaptation process to a potentially traumatic event such as an SCI may extend over several years (Dijkers, 2005), individuals already show signs of positive adjustment shortly after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing average changes in adaptation outcomes have identified increases in life satisfaction between rehabilitation admission and discharge (van Koppenhagen et al, 2009; White et al, 2010) but inconsistent findings regarding mental health. Some studies have identified no average changes in mental health (van Leeuwen et al, 2015), others have reported average decreases in depressive symptoms but not in anxiety symptoms (Kennedy et al, 2010), and others have found average decreases in both depressive and anxiety symptoms during inpatient rehabilitation (van Diemen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%